2019
DOI: 10.1016/j.visres.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Radial frequency patterns describe a small and perceptually distinct subset of all possible planar shapes

Abstract: Radial frequency patterns describe a small and perceptually distinct subset of all possible planar shapes.Schmidtmann, GThe visual system is exposed to a vast number of shapes and objects. Yet, human object recognition is effortless, fast and largely independent of naturally occurring transformations such as position and scale. The precise mechanisms of shape encoding are still largely unknown. Radial frequency (RF) patterns are a special class of closed contours defined by modulation of a circle's radius. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Despite this, the representation of shape in the PLOS COMPUTATIONAL BIOLOGY human visual system remains elusive, and the basis for shape similarity judgments remains unclear. In part, this is due to the numerous potential shape descriptors proposed in the past, including simple metrics, like solidity [36], and contour curvature [39], and more complex metrics like shape context [38], part-based ones [1,85], Fourier descriptors [41,100,101], radial frequency components [82,102], shape skeletons [40,46,98,99,[103][104][105][106][107], linearity [108] convexity [109][110][111][112], triangularity [113], rectilinearity [114], information content [115,116] and models based on generalized cylinders for describing 3D animal-like objects [117]. While it is widely believed that human shape representations are multidimensional, to date there has been no comprehensive attempt to implement this idea in a concrete image-computable model.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the representation of shape in the PLOS COMPUTATIONAL BIOLOGY human visual system remains elusive, and the basis for shape similarity judgments remains unclear. In part, this is due to the numerous potential shape descriptors proposed in the past, including simple metrics, like solidity [36], and contour curvature [39], and more complex metrics like shape context [38], part-based ones [1,85], Fourier descriptors [41,100,101], radial frequency components [82,102], shape skeletons [40,46,98,99,[103][104][105][106][107], linearity [108] convexity [109][110][111][112], triangularity [113], rectilinearity [114], information content [115,116] and models based on generalized cylinders for describing 3D animal-like objects [117]. While it is widely believed that human shape representations are multidimensional, to date there has been no comprehensive attempt to implement this idea in a concrete image-computable model.…”
Section: Discussionmentioning
confidence: 99%
“…However, Wilkinson et al (1998) explained the mathematical limitations of RF patterns and stressed their differences from Fourier shape descriptors, which can in principle be used to create any kind of closed, two-dimensional shape. The representational and perceptual limitations of RF patterns were pointed out by Schmidtmann and Fruend (2019), who demonstrated that only a very small subset of natural and synthetic shapes can be reliably represented by RF compound patterns and that this subset is perceptually distinct. However, despite these limitations, the visual performances of RF patterns that have been observed in a wide range of stimulus conditions have provided deep insight into the shape processing mechanism of the visual system.…”
mentioning
confidence: 99%
“…In the present experiments, the participants were familiar with the circle, and thus, may have paid more attention to evaluating illusion magnitude (Shulman, 1992). The other explanation may be that neurons sensitive to curvature importantly for processing visual form (Salmela, Henriksson & Vanni, 2016;Schmidtmann & Fruend, 2019). Consequently, the size of the test gure would more accurately re ect the target, and hence, the magnitude of the quasi-Delboeuf illusion would be smaller for circles than for regular octagons or regular hexagons.…”
Section: Contour Attractionmentioning
confidence: 84%